Tzanck cytology smear in diagnosis of cutaneous talaromycosis penicilliosis - Lai, Shau-Kong; Abd Rauf, Nurhafidzah; Preet, Kaur Roshen; Tan, Lii-Jye (Scientific Scholar, 2021)
Talaromyces marneffei infection is an AIDS-defining illness in South and Southeast Asia. Travel-related talaromycosis is being increasingly recognized in non-endemic areas too. It is a potentially fatal infection with rapid deterioration, if left untreated. Usage of Tzanck cytology smear for rapid diagnosis of T. marneffei is rarely described. In this case study, we report a man who presented with altered behaviour, headache, fever and cutaneous lesions. Tzanck smear test, skin biopsy and blood culture showed presence of T. marneffei. The cytomorphology findings of T. marneffei in Tzanck cytology smear were described. In conclusion, Tzanck smear is a simple and inexpensive test in establishing a rapid clinical diagnosis of talaromycosis before the culture is reported.